Energy-positive sewage sludge pre-treatment with a novel ultrasonic flatbed reactor at low energy input. (September 2018) - Lippert, Thomas; Bandelin, Jochen; Musch, Alexandra; Drewes, Jörg E.; Koch, Konrad
Graphical abstract: Highlights: Performance assessment of a novel ultrasonic flatbed reactor for sludge treatment. Methane yield enhancement for sludges with high total solid contents (4.4 – 6.7%). Low energy inputs (200 kJ/kgTS ) significantly increased methane yields (max. + 12%). High inputs (≥2, 000 kJ/kgTS ) enhanced kinetics, but were limited to similar gains. Positive energy balance of sonication only at 200 kJ/kgTS (122% recovery at max.). Abstract: The performance of a novel ultrasonic flatbed reactor for sewage sludge pre-treatment was assessed for three different waste activated sludges. The study systematically investigated the impact of specific energy input (200 – 3, 000 kJ/kgTS ) on the degree of disintegration (DDCOD, i.e. ratio between ultrasonically and maximum chemically solubilized COD) and methane production enhancement. Relationship between DDCOD and energy input was linear, for all sludges tested. Methane yields were significantly increased for both low (200 kJ/kgTS ) and high (2, 000 – 3, 000 kJ/kgTS ) energy inputs, while intermediate inputs (400 – 1, 000 kJ/kgTS ) showed no significant improvement. High inputs additionally accelerated reaction kinetics, but were limited to similar gains as low inputs (max. 12%), despite the considerably higher DDCOD values. Energy balance was only positive for 200 kJ/kgTS -treatments, with a maximum energy recovery of 122%. Results suggest that floc deagglomeration rather than cell lysis (DDCOD  = 1% – 5% at 200 kJ/kgTS ) is the key principle of energy-positive sludge sonication.